An Approach Towards Image Encryption and Decryption using Quaternary Fractional-Linear Operations - Kovalchuk, Anatoliy; Izonin, Ivan; Gregush ml, Mihal; Lotoshynska, Natalia (Procedia computer science, 2019)
The problem of unauthorized access to various content is an important task for the present. It becomes even more acute when using the existing toolkit for the processing and transmission of encrypted images with the fluctuation intensity function. The authors developed a modification of the RSA algorithm to use it in relation to the above-mentioned images. It is proposed a conceptual view for the joint use of quaternary fractional-linear transformations with elements of the basic RSA algorithm. The application of this mathematical apparatus in the basic RSA algorithm avoids contours of image objects in an encrypted sample. In addition, this combination provides additional stability to the basic RSA algorithm for unauthorized decryption. The simulation of the method was carried out in two described by the authors algorithms: using one line and four lines of the image matrix, for grayscale and color images. The high efficiency of the developed method for avoiding contours of objects on encrypted images has been confirmed. In both cases, contours after applying encryption procedures do not appear. The reverse procedure allows to get an image without visible distortion.